Forecasting Relationship between Annual Income and Annual Expenditure in Nigeria Educational Sector - Jude, Iroka; O, Akpienbi I. (Darul Yasin Al Sys, 2024)
This study investigates the relationship between annual income and annual expenditure using regression analysis. Data spanning multiple years were analysed to understand the dynamics between income and expenditure. The analysis revealed a strong positive correlation between income and expenditure, indicating that higher income levels are associated with increased spending. Despite non-normal distribution, the regression model effectively captured the relationship between income and expenditure, offering insights into consumer behaviour. Forecasted expenditure values based on the regression model provide valuable information for future planning and decision-making. Overall, the study emphasizes the importance of understanding the link between income and expenditure and demonstrates the utility of regression analysis in economic research. Despite deviations from normality, the regression model effectively captures the essence of the income-expenditure relationship, facilitating accurate predictions of future spending trends. The findings offer valuable insights for policymakers, businesses, and individuals alike, highlighting the significance of prudent financial planning and resource allocation. By understanding the dynamics of income and expenditure, stakeholders can make informed decisions to promote economic stability and enhance overall well-being.